Quantitative Easing: The Challenge for Households Long-term Savings and Financial Security - Christian Thimann (Center for Economic Studies and ifo Institute (CESifo), 2016)
The extremely low long-term interest rates in capital markets, to a relevant extent induced by quantitative easing, imply significant challenges for retirement saving and the stability of households' purchasing power over the long-term. The reason is that prices for the two most important long-term savings objectives – housing and healthcare – are rising substantially, while long-term return in safe instruments is virtually zero. Savers face a major dilemma: either they miss long-term savings objectives and see purchasing power decline, or they compromise financial security and invest in highly volatile assets, such as equity, whose return is highly uncertain and potentially negative. This issue is especially relevant in Europe where equity markets are much less developed and where some major European indices are still today trading below the levels reached in the year 2000.
Keywords: E30; E43; E50; 330; quantitative easing; savings; purchasing power